Immunoradiometric measurement of the factor VIII procoagulant antigen. - Lazarchick, J (1978)
A fluid-phase immunoradiometric assay has been developed which identifies an antigen on the Factor VIII (antihemophilic factor) procoagulant protein. This sensitive and quantitative assay is not influenced by levels of Favor VIII-related antigen (von Willebrand factor) or other plasma proteins. There is a close correlation of procoagulant activity and immunologically detectable protein in normal and von Willebrand's disease plasmas. In contrast, several different patterns have been identified in hemophilic plasmas. Neither procoagulant activity nor procoagulant antigen is detectable in plasmas from patients with severe classic hemophilia. Patients with mild and moderate hemophilia have either comparable plasma concentrations of procoagulant activity and procoagulant antigen or relatively greater levels of immunologically detectable protein.